Thyroid Storm Complicating Pregnancy, A Case Report and Management - Alev Aydın; Melehat Dönmez; Yavuz Aydın; Güner Karatekin; Günseli Özdemir; Özlem Oruç (Medical Network, 2008)
The incidence of hyperthyroidism in pregnancy is between 0,05 % and 0,2%. Graves disease is the most common cause of hyperthyroidism in pregnancy. Decrease in Thyroid Stimulating Hormone(TSH) levels and increase in free thyroxine levels are used for diagnosis of thyrotoxicosis. If hyperthyroidism is not treated during pregnancy, these pregnancies are prone to both maternal and fetal complications. Here we present a case of thyrotoxicosis with some maternal and fetal complications. 37 year old woman ,G4P2A1 with 28 - 29 weeks of pregnancy admitted to our clinic with complaints of back pain, painful uterine contractions and low pelvic pressure. Her blood pressure was 200/120mmHg, pulse rate was 120/min. She had tremor and exolphtalmic eyes, diffuse edema on legs. On suspect of hyperthyroidism she was told to uncover her neck. A diffuse goiter on neck was examined. Her thyroid hormones were sent for control. Thyroid hormone levels were TSH:0,009 uIU/ml, Free T3 :17,2 pg/ml (2-4,4),Free T4:>6 ng/ml (0,9-1,7). On emergency consultation, she had the diagnosis of Basedow Graves complicated with thyroid storm and undertaken to emergency treatment. Her blood glucose levels were checked four times in a day regularly and she had fasting blood glucose levels >120mg/dl and postbrandial blood glucose levels >200mg/dl and with the diagnosis of gestational diabetes, she has been started on ınsuline therapy. After 3 months of treatment, she gave birth to 2700gr, 44cm, Apgar 7-8 fetus. Postpartum no maternal or fetal complications were seen. Postpartum at the first week the baby had hyperthyroidism symptoms with the placental transport of autoantibodies, therefore breast feeding was stopped and checked for hormone levels regularly. The baby is now under control for the possibility of expected hypothyroidism. In uncontrolled hyperthyroidism, preeclampsia, premature birth, abruptio placenta, intrauterine growth retardation, fetal hyperthyroidism, stillbirth rates increase. These complication rates fall with the treatment of hyperthyroidism. Not only IUGR, we think gestational diabetes mellitus and macrosomic or LGA(large for gestational age) fetus could be one of the results of hyperthyroidism and high metabolic state in pregnancy. Hyperthyroidism in pregnancy is more frequent in our country and may mimic many pregnancy related conditions and should be differentiated and managed carefully.